SOSIALISASI LITERASI DASAR BAGI MAHASISWA BARU UIN KH ABDURRAHMAN WAHID PEKALONGAN - Ryan Deriansyah; Nadya Nurunnisa Febiani; Asyfia Ika Yuliani; Shilvi Aqilah; Allisa Zanuba; Elsa Maulidina; Arditya Prayogi (LPPM Universitas Bina Bangsa, 2022)
College libraries have the task of supporting the implementation of the Tridharma of Higher Education, one of which is community service. In this case the library also carries out the task of collecting, processing, storing, presenting and disseminating information to the public. That is, the library has a role in building the literate generation. An effort is needed to program activities that can improve capabilities in the field of information retrieval. It is on this basis that this library-based community service activity is carried out. This activity was carried out with the literacy socialization method as well as a library tour or library tour targeting all new students in the UIN KH Abdurrahman Wahid Pekalongan environment with the aim of gaining basic literacy skills in their academic life. From the results of the service, it was found that this activity was well received and had benefits that could be felt directly by the participants of the activity. This means that efforts to increase literacy actually need to be framed in an integrated movement, not partial, individually or determined by certain groups but must be collaborative